In Search of Cosmic-Ray Antinuclei from Dark Matter with the GAPS Experiment - Manghisoni, M.; Re, V.; Riceputi, E. (Sissa Medialab Srl, 2022)
The General Antiparticle Spectrometer (GAPS) is the first experiment optimized to identify low-energy (.0.25 GeV/n) cosmic antinuclei, in particular antideuterons from dark matter annihilation or decay. The GAPS program will deliver unprecedented sensitivity to cosmic antideuterons, an essentially background-free signature of various dark matter models, as well as a high-statistics antiproton spectrum in the unexplored low-energy range, and leading sensitivity to cosmic antihelium. GAPS is currently under construction. The first Antarctic balloon flight of GAPS is planned for late 2022, and two additional flights are planned for the coming years. Based on measurements of our custom-developed instrument technology, including large-area lithium-drifted silicon (Si(Li)) detectors and a large-acceptance time-of-flight system, as well as detailed instrument simulation and reconstruction studies, we present here the anticipated impact of the GAPS program on dark matter searches. This contribution discusses the current status of cosmic antinuclei studies while focusing on the science potential of GAPS.